Human Interface and the Management of Information. Supporting Learning, Decision-Making and Collaboration : 19th International Conference, HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, Proceedings /: Supporting Learning, Decision-Making and Collaboration : 19th International Conference, HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, Proceedings. Part II : (2017) - Unknown
No abstract available